Peluang Penerapan Desain Thinking di Industri Maritim Studi Kasus : Pencarian Jasa Docking - Bachtiar W, Marsellinus (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
The ship maintenance industry is one of the maritime sectors that supports the economy, where ships are required by regulations to dry dock periodically for repairs and maintenance to ensure their seaworthiness. From the shipowner's perspective, the need is to find a dry dock that meets both technical and economic requirements. Innovations in business processes and drydocking business models have seen various improvements, particularly in the use of technology, automation, and operational efficiency. The implementation of Design Thinking in the maritime industry is widely open, although there are challenges in its adoption, especially due to entrenched business practices and the complexity of meeting dry dock requirements. The results obtained from the observation of the implementation efforts indicate that there are opportunities for the application of new innovations in the maritime industry. This is attributed to the openness towards new technologies and business processes, especially among the next-generation leaders of companies, who belong to the millennial or Gen Z cohorts.